Indonesia's Economic Recovery Through a New Policy on Investors Based on The Perspective of Immigration Law - Asto Yudho Kartiko; Biyan Habibie; Faomasi Zalukhu (IHSA Institute, 2021)
A country's economy is affected by a variety of factors, one of which is a change in the law. Changes in the law in one country occur because of the results of a political system that adapts to global circumstances. One of the global circumstances affecting the current law change is the covid-19 pandemic that has spread to several countries, including Indonesia. During the current pandemic, Indonesia is also hit by an economic crisis. Various efforts have been carried out by the Indonesian government in the recovery of the nation's economy. One of them is through Government of Regulation Number 48 of 2021 concerning the Third Amendment of Government of Regulation Number 31 of 2013 concerning the Implementation of Act Number 6 of 2011 on Immigration. The formulation of the problems in this study is how the new policy provisions on investors in Government of Regulation Number 48 of 2021 and how the influence of new policies on investors in the Government of Regulation number 48 of 2021 on the recovery of the Indonesian economy. The results of this study are new provisions regarding Foreign Investment, namely pre-investment, foreigners who make investments are exempt from guarantors, and foreigners released from guarantors can pay immigration guarantees. The advice given for this research topic is that it should accelerate the establishment of special rules from Regulation Government Number 48 of 2021 to restore the Indonesian economy through investment from foreigners.